What influences the climate entrepreneurship? Chinese-based evidence - Li, Cai; Asim, Shoaib; Khalid, Waleed; Sibt E. Ali, Muhammad (Frontiers in Environmental Science, 2023)
Climate change is the biggest threat to the public as it threatens water scarcity, heat waves, economic losses, food insecurity, etc. Consequently, the control of climate entrepreneurship is very significant to ensure business sustainability. However, the identification of controlling measures for climate entrepreneurship remained unexplored. Therefore, the purpose of this study was to examine the influence of organizational performance, carbon management practices, and attitudes towards emission trading schemes on climate entrepreneurship. The study is based on 180 respondents from large Chinese firms. Using Structural Equation Modeling, the results report a significantly negative influence of organizational performance, carbon management practices, and attitudes towards emission trading schemes on climate entrepreneurship. This suggests to the management and policymakers that an increase in organizational performance, carbon management practices, and attitude towards emission trading schemes brings a significant decline in climate entrepreneurship and thus, ensures a sustained business environment. Chinese policy makers are very keen to adopt emission trading scheme and by the implication of articulate results can help them to attain their climatic goals.